Los efectos del Tratado de Libre Comercio con Estados Unidos y los precios del maíz colombiano - Tróchez González, Johanna; Valencia Cárdenas, Marisol; Salazar, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Páginas 151-172